2005
DOI: 10.1038/sj.npp.1300843
|View full text |Cite
|
Sign up to set email alerts
|

Hydrocortisone Impairs Hippocampal-Dependent Trace Eyeblink Conditioning in Post-Traumatic Stress Disorder

Abstract: Trace eyeblink conditioning is a hippocampal-dependent associative learning task that could help evaluate hippocampal function in Posttraumatic stress disorder (PTSD). Since preclinical research has demonstrated that trace eyeblink conditioning can be pharmacologically manipulated by glucocorticoids, this task may shed light on glucocorticoid sensitivity in PTSD. This study assessed baseline and hydrocortisone-mediated changes in trace eyeblink conditioning in patients with PTSD and in healthy controls. A tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 45 publications
5
29
0
Order By: Relevance
“…In line with our findings, the hippocampus has been found to be relevant also for other anxiety disorders [62,63], conditioning paradigms [35,49,64,65,66,67,68,69] and seems to be sensitive to exposure [70], CBT treatment [30,71,72], therapy response [30] or recovery in general [73]. Furthermore, the hippocampus has been discussed with regard to the potential contribution to acquisition of irregularities in PD [15] and the optimization of exposure therapy and related learning processes [26].…”
Section: Discussionsupporting
confidence: 80%
“…In line with our findings, the hippocampus has been found to be relevant also for other anxiety disorders [62,63], conditioning paradigms [35,49,64,65,66,67,68,69] and seems to be sensitive to exposure [70], CBT treatment [30,71,72], therapy response [30] or recovery in general [73]. Furthermore, the hippocampus has been discussed with regard to the potential contribution to acquisition of irregularities in PD [15] and the optimization of exposure therapy and related learning processes [26].…”
Section: Discussionsupporting
confidence: 80%
“…Numerous other examples of enhanced peripheral GR responsiveness have also been observed (Altemus et al 2003;Golier et al 2006;Rohleder et al 2004;Strohle et al 2008;Yehuda et al 1995Yehuda et al , 1996aYehuda et al , b, 2004a. There is also evidence for enhanced responsiveness of brain GC (Grossman et al 2006;Vythilinham et al 2006;Yehuda et al 2009a, b). The neuroendocrine profile in PTSD is different from that observed in animal and human studies of stress and depression which generally consists of higher CRH, but elevated cortisol, and reduced cortisol suppression to DEX, accompanied by reduced GR responsiveness (Pariante and Lightman 2008;Strohle and Holsboer 2003).…”
Section: Hpa Axis Alterations In Ptsd: Relation To Riskmentioning
confidence: 92%
“…While animal studies have shown the involvement of stress-sensitive neurons from hippocampal CA1 and CA3 regions in trace conditioning (McEchron and Disterhoft 1997;Weiss et al 1996), human studies as well have demonstrated the critical role of glucocorticoids in eyeblink conditioning modulation. An impairment of eyeblink conditioning during pharmacologically induced mild hypercortisolism and in persons with endogenous hypercortisolism was observed for trace but not delay conditioning processes (Grillon et al 2004;Moyer et al 1990;Vythilingam et al 2006), findings supported by the high concentration of glucocorticoid receptors in the hippocampus.…”
Section: Introductionmentioning
confidence: 58%
“…Further, eyeblinks that occurred during the empty interval of 100-600 ms after the CS were considered as "nonadaptive" responses because of their poor timing relative to the CS (Grillon et al 2004;Vythilingam et al 2006). The probability of nonadaptive CRs was low and did not differ significantly between metyrapone-(mean=8%) and placebo-group [mean=7,333%; F(1,33)=0.150; p=0.700].…”
Section: Discussionmentioning
confidence: 98%